Case Report: Pulmonary mixed infection by Nocardia cyriacigeorgica, Stenotrophomonas maltophilia, and human cytomegalovirus in a patient with minimal change nephrotic syndrome - Li, Yahua; Ye, Jiaqing; Zhang, Chenfeng; Gao, Weili; Zhang, Hong; Zheng, Cuiying; Feng, Zhongjun; Song, Minghui; Hao, Jiahao; Zuo, Huifen; Zhao, Zhenjun; Guo, Yumei; et al. (Frontiers in Immunology, 2025)
To our knowledge, this is the first reported case of a pulmonary mixed infection involving Nocardia cyriacigeorgica, Stenotrophomonas maltophilia, and human cytomegalovirus (HCMV) in a patient with minimal change nephrotic syndrome (MCNS), which is of great clinical significance. We report the case of an 18-year-old male with a two-month history of MCNS who was admitted due to fever, cough, and bright red hemoptysis. Upon admission, he was treated with piperacillin/tazobactam and moxifloxacin for one week; however, the therapeutic response was suboptimal. Metagenomic Next-Generation Sequencing (mNGS) and microbiological culture of bronchoalveolar lavage fluid identified a pulmonary mixed infection involving N. cyriacigeorgica, S. maltophilia, and HCMV. Following the initiation of combination therapy with linezolid, trimethoprim-sulfamethoxazole, and ganciclovir, the patient’s condition improved markedly, and he was discharged in a stable condition. One-year follow-up revealed complete recovery with no recurrence. This case highlights the critical role of incorporating advanced molecular diagnostic tools such as mNGS into clinical practice and the need to be vigilance about opportunistic infections involving multiple pathogens, especially in patients receiving immunosuppressive therapy.